Structure based discovery of small molecule suppressors targeting bacterial lysozyme inhibitors - Voet, Arnout; Callewaert, Lien; Ulens, Tim; Vanderkelen, Lise; Van Herreweghe, Joris; Michiels, Chris W.; De Maeyer, Marc (Biochemical and Biophysical Research Communications, 2011)
The production of lysozyme inhibitors, competitively binding to the lysozyme active site, is a bacterial strategy to prevent the lytic activity of host lysozymes. Therefore, suppression of the lysozyme-inhibitor interaction is an interesting new approach for drug development since restoration of the bacterial lysozyme sensitivity will support bacterial clearance from the infected sites. Using molecular modelling techniques the interaction of the Salmonella PliC inhibitor with c-type lysozyme was studied and a protein-protein interaction based pharmacophore model was created. This model was used as a query to identify molecules, with potential affinity for the target, and subsequently, these molecules were filtered using molecular docking. The retained molecules were validated as suppressors of lysozyme inhibitory proteins using in vitro experiments revealing four active molecules. sponsorship: A.V. wishes to thank the scientific research council of the university for the postdoctoral funding. L.V. acknowledges the Flemish Institute for the Promotion of Scientific Technological Research (IWT) for the doctoral fellowship. L.C. is supported by a postdoctoral and J.M.V.H. by a doctoral fellowship of the Research Foundation-Flanders (FWO-Vlaanderen). The work was further supported by research grants from FWO-Vlaanderen (G.0363.08) and from KULeuven (IOF-HB/08/005 and METH/07/03). Inge W. Nilsen (NOF-IMA, Tromso, Norway) is acknowledged for donating the strain BL21 GOLD (DE3) PQM64. (scientific research council of the university, Flemish Institute for the Promotion of Scientific Technological Research (IWT), Research Foundation-Flanders (FWO-Vlaanderen), FWO-Vlaanderen|G.0363.08, KULeuven|IOF-HB/08/005, KULeuven|METH/07/03) status: Published